Barriers in access to healthcare in countries with different health systems. A cross-sectional study in municipalities of central Colombia and north-eastern Brazil (2014)
There are few comprehensive studies available on barriers encountered from the initial seeking of healthcare through to the resolution of the health problem; in other words, on access in its broad domain. For Colombia and Brazil, countries with different healthcare systems but common stated principles, there have been no such analyses to date. This paper compares factors that influence access in its broad domain in two municipalities of each country, by means of a cross-sectional study based on a survey of a multistage probability sample of people who had had at least one health problem within the last three months (2163 in Colombia and 2155 in Brazil). The results reveal important barriers to healthcare access in both samples, with notable differences between and within countries, once differences in sociodemographic characteristics and health needs are accounted for. In the Colombian study areas, the greatest barriers were encountered in initial access to healthcare and in resolving the problem, and similarly when entering the health service in the Brazilian study areas. Differences can also be detected in the use of services: in Colombia greater geographical and economic barriers and the need for authorization from insurers are more relevant, whereas in Brazil, it is the limited availability of health centres, doctors and drugs that leads to longer waiting times. There are also differences according to enrolment status and insurance scheme in Colombia, and between areas in Brazil. The barriers appear to be related to the Colombian system's segmented, non-universal nature, and to the involvement of insurance companies, and to chronic underfunding of the public system in Brazil. Further research is required, but the results obtained reveal critical points to be tackled by health policies in both countries. © 2014 The Authors.